1960
DOI: 10.1002/j.2050-0416.1960.tb01740.x
|View full text |Cite
|
Sign up to set email alerts
|

Beer Flavour: I. Volatile Products of Fermentation: A Review

Abstract: The flavour of beer and other fermented beverages is conditioned by the volatile components present. Many of these compounds are concentrated into the higher alcohol or fusel oil fraction. The various substances which have been identified in fusel oils are discussed together with the methods available for their analysis and the values obtained when these methods are applied to beers, wines and spirits. The biochemical pathways which have been proposed for the formation of the higher alcohols as well as diacety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1966
1966
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 73 publications
0
12
0
2
Order By: Relevance
“…A fermentação dos mostos de cana-de-açúcar, laranja e uva produzem, além do álcool etílico, seu principal produto, vários outros componentes chamados secundários, como os aldeídos, metanol, álcoois superiores, ácidos, ésteres, cetonas, fenóis, mercaptanas, entre outros (MAIA, 1994). Apesar da pequena quantidade dessas substâncias, em relação à água e ao etanol, elas são determinantes na caracterização do flavour , que é definido como sendo a mistura das sensações de aroma e sabor (STEVENS, 1960) e tem grande influência sobre a qualidade das aguardentes.…”
Section: (Recebido Para Publicação Em 4 De Dezembro De 2002 E Aprovadunclassified
See 1 more Smart Citation
“…A fermentação dos mostos de cana-de-açúcar, laranja e uva produzem, além do álcool etílico, seu principal produto, vários outros componentes chamados secundários, como os aldeídos, metanol, álcoois superiores, ácidos, ésteres, cetonas, fenóis, mercaptanas, entre outros (MAIA, 1994). Apesar da pequena quantidade dessas substâncias, em relação à água e ao etanol, elas são determinantes na caracterização do flavour , que é definido como sendo a mistura das sensações de aroma e sabor (STEVENS, 1960) e tem grande influência sobre a qualidade das aguardentes.…”
Section: (Recebido Para Publicação Em 4 De Dezembro De 2002 E Aprovadunclassified
“…Quanto maior a acidez do vinho de laranja, uva e cana, que foi respectivamente de 6,1 g de H 2 SO 4 /L; uva, 4,0; e cana, 1,7 (Tabela 1), maior a quantidade de acetaldeído nas aguardentes. Segundo Suomalainen e Lehtonen (1979), os aldeídos são de suma importância como compostos aromáticos, devido aos seus baixos valores sensoriais. A baixa acidez dos mostos de laranja e uva provoca a diminuição do pH do meio, liberando o íon H+, que reage com o íon OH + , oxidando o álcool etílico a acetaldeído.…”
Section: Aminoácidosunclassified
“…The higher alcohols, known sometimes as fusel oil, include mostly isoamyl and active amyl alcohol and smaller amounts of propyl, isopropyl, butyl, isobutyl, amyl, and phenylethyl alcohols (Davidson, 1961 ;Stevens, 1960;Vander Kloot, Tenney, and Bavisotto, 1958).…”
Section: Alcoholsmentioning
confidence: 99%
“…Fusel oils, or the higher alcohols produced during fermentation, play an important part in the bouquet of wine and the flavour of beer (Stevens, 1960). It has been reported that fusel oils are produced from the degradation of amino-acids by the Ehrlich pathway during wine fermentation (Sentheshanmuganathan & Elsden, 1958).…”
Section: Introductionmentioning
confidence: 99%